Compensated hole-entry Hybrid Journal Bearing by CFV Restrictor under Micropolar Lubricants / Nathi Ram...[et al.] - Ram, Nathi; C. Sharma, Satish; K. Rajput, Arvind (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In this work, the performance of hole-entry hybrid journal bearing compensated by constant flow valve (CFV) restrictor under micropolar lubricants has been numerically simulated. Reynolds equation for micropolar fluid lubricated bearing has been solved with finite element technique. Performance of bearing has been evaluated as a function of coupling number N² . The simulated characteristics of bearing under micropolar lubricants have been compared with similar bearing under Newtonian lubricant. The results are presented for the selected micropolar parameters N² and lm. Simulated results indicate that the bearing under micropolar lubricants exhibits the increased values of minimum fluid film thickness, stiffness and damping coefficients than similar bearing under Newtonian lubricant. Further, the coefficient of friction decreases for a bearing when it is operating under micropolar lubricant than Newtonian lubricant.